Synthesis and Photocatalytic Properties of Nitrogen Modified Titanium Dioxide - Nina Ivanova; Angelina Stoyanova; Albena Bachvarova-Nedelcheva; Reni Iordanova (Journal of Biomedical & Clinical Research)
Pure and nitrogen-doped titanium dioxide (N-doped TiO2) photocatalysts were prepared by non-aqueous sol-gel method by means of the reaction between titanium (IV) chloride (TiCl4) and C6H5CH2 OH (benzyl alcohol), used as precursors and urea serving as a nitrogen source. The phase formation and short-range order of the resulting particles were characterized by X-ray powder diffraction (XRD) and infrared (IR) spectroscopy. The crystallite size of as-prepared composite powders was in the range 12-35 nm. The aim of this work was to investigate the efficiency of N-doped TiO2 as a photocatalyst in degradation of model organic pollutants - dyes Reactive Black 5 (RB5) and Malachite Green (MG), under ultraviolet (UV) and visible (Vis) irradiation. 0ur results indicated that synthesized N-TiO2 nanocomposites slightly improved the photocatalytic activity under UV irradiation, compared to the pure titanium dioxide (TiO2), and had no effect under Vis light illumination.